The complete chloroplast genome of an ornamental orchid, Vanda coerulescens (Orchidaceae) - Wang, Xiao-ting (Mitochondrial DNA B Resour, 2020)
Though the chloroplast genomes of several Vanda species have been sequenced, there is little information about the complete chloroplast (cp) genome of Vanda coerulescens. Herein, we established the cp genome of V. coerulescens. The chloroplast genome circle was 149,410 bp in length, with the structure of an 85,954 bp large single-copy (LSC) region and a 11,526 bp small single-copy (SSC) region, which separated by two inverted repeat (IRs) regions of 25,965 bp. It encoded 130 genes, including 74 protein-coding genes, 38 tRNA genes and 8 rRNA genes. The overall GC-content of the whole plastome is 36.7%, whereas the corresponding values of the LSC, SSC, and IR regions ranged from 28.2% to 43.1%. In addition, the phylogenetic analysis base on 20 chloroplast genomes of Orchidaceae indicates that V. brunnea is closely related to V. coerulescens. This announcement of the complete V. coerulescens cp genome sequence could provide valuable information for further genetic modification and phylogenetic study in Vanda genus.